Charting the policy development process of social housing bonds in Australia through an impact narrative approach. Issue 3 (14th May 2021) - Fotheringham, Michael; Gorter, Tamlin; Badenhorst, Anne
Abstract: The Australian Housing and Urban Research Institute (AHURI) has, since its inception, prioritised policy relevance in its research. Drawing on an impact narrative approach, this paper presents a case study of the contribution of AHURI research to the development of a specific policy initiative: the Affordable Housing Bond Aggregator function of the National Housing and Finance Investment Corporation (NHFIC). The paper will explore the development of this policy initiative through a series of research projects and publications, and highlight processes of dissemination and engagement with the policy and practice community. This will reveal the value of a strong evidence‐base, and effective knowledge transfer mechanisms in the development and implementation of policy. It will also demonstrate the utility of a policy impact narrative approach in the evaluation of research impact, particularly in relation to policy development processes subject to the vagaries of politics. Abstract : This policy impact narrative presents a case study of the contribution of the research and policy engagement practices of the Australian Housing and Urban Research Institute (AHURI) to the implementation of a policy initiative. AHURI research on institutional investment in social and affordable housing refined and tested this model for financing community housing.